Mortality factors and antibiotic options in carbapenem‐resistant Enterobacterales bloodstream infections: Insights from a high‐prevalence setting with co‐occurring NDM‐1 and OXA‐48 - Palat Karnmueng; Preecha Montakantikul; Taniya Paiboonvong; Rongpong Plongla; Tanittha Chatsuwan; Supatat Chumnumwat (Wiley, 2024)
Abstract Bloodstream infections (BSI) caused by carbapenem‐resistant Enterobacterales (CRE) are associated with a high mortality rate. This study aimed to investigate factors associated with 14‐day mortality and identify a potential treatment option. A retrospective cohort study was conducted on patients with CRE‐BSI in Thailand from 2015 to 2020. The multivariate Cox proportional‐hazards model was employed to identify factors influencing 14‐day mortality. Out of 134 diagnosed cases of CRE‐BSI, the all‐cause 14‐day mortality rate was 35.1%. The most prevalent organism isolated was Klebsiella pneumoniae (85.8%), followed by Escherichia coli (11.9%). Among the 60 isolates tested for carbapenemase genes, the majority exhibited co‐occurring blaNDM‐1 and blaOXA‐48 (51.7%), followed by blaOXA‐48 (31.7%) and blaNDM‐1 (15.0%). In the multivariate analysis, neutropenia (adjusted hazard ratio [aHR] 2.55; 95% confidence interval [95%CI] 1.28-5.06; p = 0.008), sepsis/septic shock (aHR 3.02; 95%CI 1.33-6.86; p = 0.008), and previous metronidazole exposures (aHR 3.58; 95%CI 1.89-6.71; p < 0.001) were identified as independent factors for 14‐day mortality. The fosfomycin‐based regimen was found to be protective (aHR 0.37; 95%CI 0.15-0.92; p = 0.032). In patients with CRE‐BSI, particularly in regions with a high occurrence of co‐occurring blaNDM‐1 and blaOXA‐48, neutropenia, sepsis/septic shock, and previous metronidazole exposures emerged as independent risk factors for mortality. Moreover, the fosfomycin‐based regimen showed an improvement in the survival rate.